1996
DOI: 10.1083/jcb.135.6.1741
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Rabphilin-3A in cortical granule exocytosis in mouse eggs.

Abstract: Abstract. Rabphilin-3A is a putative target protein for Rab3A, a member of the small GTP-binding protein superfamily that has been suggested to play a role in regulated exocytosis in presynapses. In this study we determined the expression and the function of Rabphilin-3A in mouse eggs at fertilization. Rabphilin-3A mRNA and protein were detected by reverse transcriptase-PCR and immunoblot analysis, respectively, in metaphase II mouse eggs. Immunofluorescence analysis showed that Rabphilin-3A protein was distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Rabphilin-3A can bind not only to Rab3A but also to Rab3B (Weber et al 1996). Rabphilin-3A positively regulates exocytosis in neuroendocrine cells (Chung et al 1995, Komuro et al 1996 and cortical granule exocytosis in eggs (Masumoto et al 1996). However, we found that Rabphilin-3A is not expressed in pituitary cells (not shown).…”
Section: Discussionmentioning
confidence: 59%
“…Rabphilin-3A can bind not only to Rab3A but also to Rab3B (Weber et al 1996). Rabphilin-3A positively regulates exocytosis in neuroendocrine cells (Chung et al 1995, Komuro et al 1996 and cortical granule exocytosis in eggs (Masumoto et al 1996). However, we found that Rabphilin-3A is not expressed in pituitary cells (not shown).…”
Section: Discussionmentioning
confidence: 59%
“…Rabphilin was originally identified as a specific GTP-Rab3A-binding protein on secretory granules (1,2) that is involved in the control of regulated secretion, including neurotransmitter release and hormone secretion (3)(4)(5)(6). Recent evidence, however, has indicated that rabphilin functions independently of Rab3A.…”
Section: ؉mentioning
confidence: 99%
“…Rabphilin is a vesicle-associated protein which is recruited by rab3 and dissociates after GTP hydrolysis, and in the presence of GDI [260]. Microinjection of rabphilin or rabphilin fragments was shown to inhibit neurotransmitter release in squid giant axons and cortical granule release from mouse eggs [261,262], but both native and a membrane-anchored form of rabphilin induced insulin secretion from HIT-T15 cells [263]. RIM, on the other hand, localizes to the presynaptic active zones in synapses, but like rabphilin associates only with the GTP-bound form of rab3 [258].…”
Section: Nsf/snap and Lmamentioning
confidence: 99%